2017
DOI: 10.1016/j.epsl.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Radiative conductivity and abundance of post-perovskite in the lowermost mantle

Abstract: Thermal conductivity of the lowermost mantle governs the heat flow out of the core energizing planetary-scale geological processes. Yet, there are no direct experimental measurements of thermal conductivity at relevant pressure-temperature conditions of Earth's core-mantle boundary. Here we determine the radiative conductivity of post-perovskite at near core-mantle boundary conditions by optical absorption measurements in a laser-heated diamond anvil cell. Our results show that the radiative conductivity of Mg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…Radiative heat transfer would be another contribution to the thermal conductivity of the LM (e.g., Clark, ; Goncharov et al, ; Hofmeister, ; Keppler et al, ). Recent optical measurements on Fe‐bearing PPv and Brg showed that the radiative thermal conductivity ( κ rad ) of PPv is smaller than that of Brg (Lobanov et al, ). This suggests that the difference in the total thermal conductivity ( κ tot = κ lat + κ rad ) between PPv and Brg could be smaller than the difference in the lattice components only.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiative heat transfer would be another contribution to the thermal conductivity of the LM (e.g., Clark, ; Goncharov et al, ; Hofmeister, ; Keppler et al, ). Recent optical measurements on Fe‐bearing PPv and Brg showed that the radiative thermal conductivity ( κ rad ) of PPv is smaller than that of Brg (Lobanov et al, ). This suggests that the difference in the total thermal conductivity ( κ tot = κ lat + κ rad ) between PPv and Brg could be smaller than the difference in the lattice components only.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the difference in the total thermal conductivity ( κ tot = κ lat + κ rad ) between PPv and Brg could be smaller than the difference in the lattice components only. Here, using a model for the κ rad constructed by Lobanov et al (), the κ tot of Mg‐PPv and Mg‐Brg at P CMB at the LM temperatures are estimated (Figure ). It is found that κ rad is not quite significant compared to κ lat in both phases but has nonnegligible contributions to κ tot .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is justified by the d 5 Tanabe‐Sugano diagram as well as the similarity in 10Dq of LS NAL and Bdgm. In further support, an absorption band centered at ~17,500 cm −1 is present in the absorption spectra of LS Fe 3+ ‐bearing Mg 0.6 Fe 0.4 SiO 3 post‐perovskite at 130 GPa and 300 K [ Lobanov et al ., ] which resembles NAL and Bdgm in the distribution of iron in the crystal structure [ Hsu et al ., ; Wu et al ., ; Yu et al ., ]. It is clear, however, that the intensity of the 2 T 2g → 2 T 1g ( 2 A 2g ) band is proportional to iron concentration at the octahedral site; thus, a substantial amount of LS Fe 3+ (~10 mol.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal field splitting energies of iron in an octahedral crystal field of NAL (this study), post‐perovskite (Ppv) [ Lobanov et al ., ], and siderite [ Lobanov et al ., ] as deduced from optical absorption measurements in DACs at 300 K. Red and blue horizontal bars show high and low spin values, respectively. The crystal field splitting energy of LS Fe 3+ in Bdgm is computed in this work (Figure ).…”
Section: Discussionmentioning
confidence: 99%